A systematic review of current understandings of employability. Issue 8 (16th November 2016) - Williams, Stella; Dodd, Lorna J.; Steele, Catherine; Randall, Raymond
Abstract : A theoretical framework is essential for the effective evaluation of employability. However, there are a wide range of definitions of employability coexisting in current literature. A review into existing ways in which employability has been conceptualised is needed to inform a better understanding of the nature of contributions made by various employability development opportunities, and appropriate assessment of these contributions. A systematic review is presented, assessing the similarities and differences between the components of employability conceptualisations, focusing on employability at an individual level. Relevant publications were identified through a sensitive search strategy of eight electronic bibliographic databases from 1960 to 2014. Data were extracted from 16 eligible manuscripts. Capital, career management and contextual dimensions were identified as unifying themes in these components. Findings indicate that success in developing employability needs to be contextualised within a conceptualisation of employability as a multifaceted construct.